Peningkatan Daya Saing Siswa SMK Melalui Pelatihan Bahasa Inggris Untuk Dunia Kerja - Riri Narasati; Ryan Hamonangan; Achmad Fajar; Adinda Aulia Putri (AMMA : Jurnal Pengabdian Masyarakat, 2024)
English language skills are a key factor in improving the competitiveness of Vocational High School (SMK) graduates in an increasingly competitive and globalized world of work. This article discusses various strategies that can be applied to improve the English language competence of SMK students to be better prepared to face industry challenges. The approaches used include communication-based learning, utilization of technology in the learning process, and integration of English materials with the needs of the industrial world. In addition, intensive training programs and English language certification are strategic steps to improve students' abilities. This research shows that interactive and contextual learning methods are able to increase student motivation and understanding. project-based, workplace simulation, and the use of digital platforms have proven effective in improving students' communication skills. In addition, industry involvement in the learning process through internship programs and cooperation with educational institutions also has a positive impact on the job readiness of graduates. With an increase in English competency, SMK graduates are not only more confident in facing the world of work, but also have a greater chance of getting a job in a multinational company or working abroad. Therefore, improving the quality of English learning in SMK should be a major concern in order to create competitive human resources who are ready to compete in the era of globalization.